THE STATE OF BASIC EDUCATION IN NIGERIA BORDER COMMUNITIES - BELLO Bolanle Muhinat (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2021)
The study investigated the state of basic education in the Nigerian international border communities of Sokoto State. A descriptive survey research design was adopted for the study. A multistage sampling technique was adopted for the selection of  597 out of 3,876 respondents. A 29 items four-point-Likert scale Researcher’s designed questionnaire that was translated into Arabic and Hausa languages with psychometric properties of content validity 0.80, 0.75, and 0.87and a reliability coefficient of 0.76, 0.82, and 0.71 while the interview items have a content validity of 0.77 and a reliability coefficient  0.78 was used to elicit the needed data. descriptive and Inferential statistic was used to analyze the data. Findings revealed that parental, teachers, governmental, and facilities factors pose challenges to basic education in the border areas, among others. Educational policymakers are recommended to take necessary measures to decentralized the curriculum of the education system in Nigeria to takes care of the educational needs of a different society.